A Review on Climate-Smart Organic Agriculture: Climate Change Resilience, Role of Technology and Future Directions of Sustainable Agriculture - Yumkhaibam Ambika Devi; Sahil Raj; Munish Kaundal (Archives of Current Research International, 2025)
Climate change presents a serious risk to worldwide food security, farming and sustainability. Organic farming, focusing on ecological principles and minimizing the use of synthetic inputs, has emerged as a viable method to alleviate the effects of climate change. This review paper explores the concept of Climate smart organic agriculture (CSOA), which integrates climate-smart practices into organic farming systems. By combining the strengths of Climate-smart agriculture and organic farming, CSOA offers a holistic solution to address the challenges of climate change and food security. This review paper gives valuable insights into the potential of CSOA, it’s importance, status of organic farming on both a global scale and within India, exports and consumption of organic products, conviction, nutrient management, problems and future synergies and approach that can be made to help foster a more sustainable and robust environment and agricultural future.